Analisis Pengaruh Literasi Keuangan Syariah, Religiusitas, Inflasi Terhadap Minat Beli Cash Waqf Linked Sukuk pada Gen Z Kota Bogor - Maulana Ja'far Shodik; Nurizal Ismail; Solahuddin Al-Ayubi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research investigates the influence of Sharia financial literacy, religiosity, and inflation on the purchase intention of Cash Waqf Linked Sukuk (CWLS) among Generation Z in Bogor City. Using a questionnaire and Structural Equation Modeling - Partial Least Square analysis, primary data were collected from 263 respondents. The results show that Sharia financial literacy and religiosity have a significant positive influence on the purchase intention of CWLS, while inflation also has a significant effect. This indicates the importance of understanding Sharia finance and levels of religiosity in enhancing the purchase intention of CWLS among Generation Z. These findings underscore the need for Sharia financial education and better religious understanding to support the growth of investments in Sharia financial instruments in the future.